2002
DOI: 10.1051/0004-6361:20021146
|View full text |Cite
|
Sign up to set email alerts
|

Coronal density diagnostics with Helium-like triplets: CHANDRA–LETGS observations of Algol, Capella, Procyon,ϵ Eri,α Cen A&B, UX Ari, AD Leo, YY Gem, and HR 1099

Abstract: Coronal density diagnostics with Helium-like triplets: CHANDRA-LETGS observations of Algol, Capella, Procyon, epsilon Eri, alpha Cen A&B, UX Ari, AD Leo, YY Gem, and HR 1099 Ness, J.-U.; Schmitt, J.H.M.M.; Burwitz, V.; Mewe, R.; Raassen, A.J.J.; van der Meer, R.L.J.; Predehl, P.; Brinkman, A.C. Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 37 publications
8
48
0
Order By: Relevance
“…This ratio is also sensitive to density and temperature. Interference with density effects is not severe as Ness et al (2002a) found low density limits for almost all stellar coronae. In Fig.…”
Section: He-like Line Ratio F/rmentioning
confidence: 67%
See 1 more Smart Citation
“…This ratio is also sensitive to density and temperature. Interference with density effects is not severe as Ness et al (2002a) found low density limits for almost all stellar coronae. In Fig.…”
Section: He-like Line Ratio F/rmentioning
confidence: 67%
“…From the response matrices effective areas were calculated and stored in ASCII files which are used as look-up tables for converting measured line counts into line fluxes. Most of the LETGS data included have been introduced by Ness et al (2002a) and for details on the data reduction we refer to that paper (effective areas from Deron Pease, Aug. 2002).…”
Section: Reduction Of the Raw Datamentioning
confidence: 99%
“…All but one of the CTTS for which the O vii triplet lines were detected showed cool plasma with high density, n e > 10 11 cm −3 (Kastner et al 2002;Stelzer & Schmitt 2004;Schmitt et al 2005;Günther et al 2006;Argiroffi et al 2007;. In contrast, the cool quiescent plasma of active stellar coronae is always dominated by low densities (n e < ∼ 10 10 cm −3 , Ness et al 2002;Testa et al 2004a). This basic difference suggests that the high-density cool plasma in CTTS is not coronal plasma but plasma heated in accretion shocks.…”
Section: Article Published By Edp Sciencesmentioning
confidence: 97%
“…If low-level emission is made up of flares as the one discussed in this paper, then densities derived spectroscopically from the timeintegrated spectrum across the entire flare should be similar to densities measured in active stars during quiescence. For the Proxima Centauri flare, we obtained an average characteristic density from the O  triplet of log n e = 10.50 +0.32 −0.25 , while, for example, the low-level YY Gem spectrum reveals a similar value, namely log n e = 10.35 +0.13 −0.45 , as do many other active main-sequence stars (Güdel et al 2001a;Ness et al 2002).…”
Section: Small Flares and Coronal Heatingmentioning
confidence: 99%